2015
DOI: 10.1111/jnc.13079
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and metabolism of fructose by rat neocortical cells in vivo and by isolated nerve terminals in vitro

Abstract: Fructose reacts spontaneously with proteins in the brain to form advanced glycation end products (AGE) that may elicit neuroinflammation and cause brain pathology, including Alzheimer’s disease. We investigated whether fructose is eliminated by oxidative metabolism in neocortex. Injection of [14C]fructose or its AGE-prone metabolite [14C]glyceraldehyde into rat neocortex in vivo led to formation of 14C-labeled alanine, glutamate, aspartate, GABA, and glutamine. In isolated neocortical nerve terminals, [14C]fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
(124 reference statements)
0
20
1
Order By: Relevance
“…While recent studies have reported fructose metabolism in some regions of the brain that express khk (including the eye, cortex, and the rostral ventrolateral medulla) (Hassel et al, 2015; Meakin et al, 2007; Wu et al, 2014), this study reveals a more pervasive capacity for multiple brain regions for fructose metabolism. Furthermore, these studies revealed for the first time that KHK activity in the mouse brain increased on a high fructose diet.…”
Section: Discussioncontrasting
confidence: 55%
“…While recent studies have reported fructose metabolism in some regions of the brain that express khk (including the eye, cortex, and the rostral ventrolateral medulla) (Hassel et al, 2015; Meakin et al, 2007; Wu et al, 2014), this study reveals a more pervasive capacity for multiple brain regions for fructose metabolism. Furthermore, these studies revealed for the first time that KHK activity in the mouse brain increased on a high fructose diet.…”
Section: Discussioncontrasting
confidence: 55%
“…Fructose is phosphorylated to fructose-1-phosphate and then catabolized to dihydroxyacetone phosphate and GA by liver aldolase B 41 , and GA promotes the formation of GA-AGEs. Moreover, previous studies reported that aldolase B was not expressed in the rat brain 42 , whereas fructose-1-phosphate cleavage (aldolase) activity has been detected in the human brain 43 .…”
Section: Discussionmentioning
confidence: 97%
“…Fructose is phosphorylated to fructose-1-phosphate and then catabolized to dihydroxyacetone phosphate and GA by aldolase B [ 33 ], and then GA promotes the formation of TAGE. Moreover, it has been reported that aldolase B is not expressed in the rat brain [ 34 ], and fructose-1-phosphate cleavage (aldolase) activity has been detected in the human brain [ 35 ]. However, it is thought that the progression of AD will take over 10 years because the enzyme expression level is considered to be very low.…”
Section: Discussionmentioning
confidence: 99%